Biovalorization of food wastes by anaerobic acidification processes - Lopes, Maria dos Anjos de Jesus Barros Monteiro (2017)
Biodegradation is an eco-friendly option for the disposal and recovery of organic waste, including food waste (FW). These residues can be treated and recovered through anaerobic digestion processes, thereby reducing their pollutant content and, at the same time, producing high value-products such as volatile fatty acids (VFA). These compounds resulting from acidogenic fermentation are the preferred carbon sources for the production of added-value products, namely polyhydroxyalkanoates (PHA) or bioenergy, in the form of methane or hydrogen. In this work, it was studied the acidogenic fermentation of several organic residues, such as the organic fraction of municipal solid waste (OFMSW), waste from the tomato processing industry (TW), coffee grounds waste (CG) and waste activated sludge (WAS) from a wastewater treatment plant. The assays were performed in batch and semi-continuous reactors, either in mono- or co-digestion assays, in order to assess and optimize its potential for VFA production. In these tests, the effects of various parameters, such as 1) total solids (TS) content in the reactor, 2) alkalinity addition, 3) organic loading rate (OLR) applied and 4) carbon-nitrogen ratio (C:N) were studied. In the mono-digestion assays, a very distinct behavior was observed in the four substrates studied, with a substantially higher acidification rate for TW (49 %) and OFMSW (41 %) than for CG (10 %) and WAS (6 %). It was also observed that in the co-digestion assays, the assay with the highest percentage of TW (75 %) and GC (25 %) showed the highest acidification degree (57 %), confirming the synergy that occurred with this mixture. Out of the three kinetic models used to study the co-digestion performance between the two major residues in Cape Verde (OFMSW and WAS), the model that presented the best correlation to obtain the methanogenic potential was exponential Curve factor model. The values for the methanogenic rate constant increased with the increase of OFMSW in the mixture, with the maximum experimental value of kM (0.27 d-1) obtained in the 75 % OFMSW assay. It was also found that, despite the low biodegradability of WAS, this substrate promoted the stability of the OFMSW digestion process in this assay, thus avoiding the inhibition of methane production due to low pH values and high concentrations of VFA, as verified experimentally in the OFMSW mono-digestion test. Thus, the kinetic study provided a simple and useful tool to predict reactor performance with respect to methane production, taking into account the proportions of each of the co-substrates, and under the conditions applied. Analyzing the results of the response surfaces obtained for the OFMSW digestion assays, it has been demonstrated that the increase in the TS reactor content led to a decrease in the acidification degree whereas the increase in the alkalinity addition led to the increase of the degree of acidification. Therefore, the highest degree of acidification (78 %) was obtained at the lowest TS reactor content (5 %) and the highest alkalinity addition (50 gCaCO3.L-1). However, depending on the ultimate use of the produced VFA mixture, the conditions presenting the highest VFA content (99 %) with high propionic acid concentration (VFA mixture more suitable for the production of high quality PHA), were the intermediate TS reactor content (8 %). From the response surfaces obtained, it was also observed that all response variables under study (VFA production, degree of acidification and effluent quality) presented a higher dependency on TS reactor content than on initial alkalinity addition. The FORSU acidogenic fermentation process was further developed in a semi-continuous CSTR reactor, which was operated under long-term and several operational conditions (organic load between 3.0 - 6.5 g COD L-1 and alkalinity between 2.0 - 5.0 g CaCO3L-1).The operational condition correspondent to of 6.0 g COD L-1d-1 and the alkalinity of 2.5 g CaCO3 L-1, was the condition where the highest degree of acidification (59 %), the best effluent quality In terms of VFA (66 %), and a good odd-to-even ratio in VFA (0.44) were achieved. In general, the increase on the organic load applied led to the increase of VFA, with acetic, propionic and butyric acids being always the predominant species in all experimental stages. The acidified effluent in the anaerobic process was then used as substrate in SBR reactors operated for the selection of mixed microbial cultures with high capacity for PHA accumulation, where it was applied a regime of dynamic feeding (feast/famine) under aerobic conditions. Three organic loads and two C:N ratios were studied, in order to evaluate the enrichment potential of the microbial mixed culture. During the process, all tested conditions showed a COD removal efficiency higher than 80 % with a PHA accumulation capacity between 17 % and 53 %. In PHA accumulation studies carried out in fed-batch reactors, three different pH values, between 7 and 8.5 were studied, where PHA accumulation was more favorable at neutral pH, , resulting in a PHA content of 25 % (w/w). The HB monomer was the main compound of the polymer synthesized from acidified OFMSW. Based on these results, it can be concluded that organic waste from food sources can be treated by biological processes, as a conventional waste treatment, and at the same time can be converted into value-added materials.